1993
DOI: 10.1152/jn.1993.70.5.1723
|View full text |Cite
|
Sign up to set email alerts
|

Role of the caudal fastigial nucleus in saccade generation. I. Neuronal discharge pattern

Abstract: 1. The effects of lesions in both human and nonhuman primates have implicated the cerebellum in the control of rapid eye movements, i.e., saccades. To examine the neural substrate of this control, we recorded the discharge patterns of cerebellar output cells in the fastigial nucleus while monkeys tracked a small, jumping spot of light. 2. In the caudal fastigial nucleus, neurons discharged for saccades in one or several directions. All exhibited a burst. Some also exhibited a saccade-related pause in firing ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
175
2
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 269 publications
(200 citation statements)
references
References 0 publications
21
175
2
2
Order By: Relevance
“…For example, numerous studies have demonstrated that schizophrenic subjects display abnormalities in smooth pursuit eye movements (Holzman et al 1973;Hutton and Kennard 1998;Levy et al 1994). The fastigial nucleus, the principal target of efferents from the cerebellar vermis (Ito 1984), is activated during pursuit eye movements (Fuchs et al 1993;Vilis and Hore 1981). Thus, the DA innervation of the primate cerebellar vermis described in the present report may reveal a new locus of action for DA in the pathophysiology of schizophrenia.…”
Section: Discussionsupporting
confidence: 53%
“…For example, numerous studies have demonstrated that schizophrenic subjects display abnormalities in smooth pursuit eye movements (Holzman et al 1973;Hutton and Kennard 1998;Levy et al 1994). The fastigial nucleus, the principal target of efferents from the cerebellar vermis (Ito 1984), is activated during pursuit eye movements (Fuchs et al 1993;Vilis and Hore 1981). Thus, the DA innervation of the primate cerebellar vermis described in the present report may reveal a new locus of action for DA in the pathophysiology of schizophrenia.…”
Section: Discussionsupporting
confidence: 53%
“…The Purkinje cells of vermis VI and VII project to the caudal part of the fastigial nucleus, which projects to the vestibular nuclei and saccade-related brainstem nuclei (Noda et al 1990). Electrophysiological experiments and clinical studies suggest that the vermis VI and VII are involved in the direction-selective control of saccade metrics and in saccadic adaptation (Kase et al 1980;Suzuki and Keller 1988;Fuchs et al 1993). Disrupting the posterior vermis, especially area VI, VII and paravermis, in humans using transcranial magnetic stimulation also suggest that these areas are related to the execution of visuallyguided saccades (Hashimoto and Ohtsuka 1995).…”
Section: Cerebellar Activationmentioning
confidence: 99%
“…Anatomical and physiological studies have separated the fastigial nucleus into rostral and caudal subdivisions (Noda et al, 1990;Buttner et al, 1991). Neurons of the caudal fastigial nucleus are modulated during saccadic or smooth pursuit eye movements (Gardner and Fuchs, 1975;Buttner et al, 1991;Fuchs et al, 1993). In contrast, the rostral division is populated by neurons that are modulated by vestibular stimulation but do not show sensitivity to eye movements (Gardner and Fuchs, 1975;Buttner et al, 1991;Siebold et al, 1997).…”
Section: Role Of Fastigial Neurons In Motion Detectionmentioning
confidence: 99%